Effectiveness of Prenatal Class Participation on Maternal Anxiety: A Scoping Review - Rahmawati Rahmawati; Asri Hidayat; Endang Koni Suryaningsih (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Pregnancy-related anxiety is a common condition that can negatively affect both maternal and fetal health. This type of anxiety has been associated with a higher risk of complications such as premature birth and low birth weight. One intervention shown to be effective in reducing anxiety during pregnancy is prenatal education through structured classes for expectant mothers.Method: The scoping review adapted the PICO (Population, Intervention, Comparison, Outcome). Framework and was systematically reported using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flowchart, then selected from the PubMed, Biomed Central, Wiley Online Library, and ResearchGate databases. A total of 2.078 articles were screened using inclusion and exclusion criteria, resulting in 16 articles to be reviewed. These were then further selected by assessing the quality of the articles using the Critical Appraisal JBI (Joanna Briggs Institute) Checklist based on the type of research from the reviewed articles.Result: Five main themes emerged from the reviewed studies: the role of prenatal classes in reducing anxiety, their impact on birth outcomes and maternal-infant health, the use of technology-based and online learning platforms, maternal mental health during pregnancy and postpartum, and various models and approaches in delivering prenatal education. Both in-person and online formats were found to be beneficial, especially when tailored to the individual needs and circumstances of pregnant women. Prenatal education classes are an effective strategy to lower anxiety levels during pregnancy and to improve maternal readiness for childbirth. Additionally, such education supports better health outcomes for both mother and baby. The delivery method whether face-to-face or digital should be selected based on the specific needs of the participants to maximize the benefits of the program.